Clasificación ABC multicriterio: tipos de criterios y efectos en la asignación de pesos (2011)
ABC classification is traditionally performed in companies in order to define and implement an inventory control policy for all the products within the same category. The classification of products into categories is done according to their importance or relevance for some kind of criteria, usually the consumption or annual usage (for raw materials or spare parts) or demand or annual sales (for finished goods) using the well-know Pareto´s principle. However, sometimes it is highly recommended and necessary to use additional criteria in order to make a more effective differentiation of stocks. Therefore, this paper presents a collection of useful criteria for ABC classification; describes its meaning and how it must be measured. Additionally, an example of a critical stage of a classification ABC with three criteria, shows that depending on the weights assigned and the characteristics of the products included in the classification process, the validity of some criteria are lost in the analysis.